Didactic strategy for the development of mathematics learning at the higher level - Riveros Fernández, Alfredo Honorato (2022)
The teaching of mathematics at the university level has aroused research interest in recent years due to the presence of active and innovative teaching strategies that have shown substantive improvements in learning achievement. In this way, the objective of the study was to analyze the relevance of the teaching strategy for the development of mathematics learning at the higher level. The methodology was based on a qualitative and quantitative perspective; both students and university teachers could be surveyed and interviewed. The results showed that many teachers use outdated teaching strategies and do not show technological mastery in the development of classes, as well as formulate inadequate perceptions of the students' ability to understand mathematics. It was possible to conclude the urgent need to implement educational practice by strengthening the professional skills of teachers, both pedagogical, digital and investigative.